Theory about biosphere of V.I.Vernadskiy and contemporary ecologo-economic knowledge - S. M. Sukhorukova; L. L. Kapinova (Тонкие химические технологии, 2010)
In this article the biographic review of the life of V.I. Vernadsky is proposed. The principal stages of his scientific work are shown. Besides, examples of using his biosphere theory for the formulation of ecologo-economic principles of wildlife management are described.